Dislocation formation in heavily As‐doped Czochralski grown silicon. Issue 8 (24th April 2017) - Stockmeier, L.; Lehmann, L.; Miller, A.; Reimann, C.; Friedrich, J.
Abstract : During growth of heavily n‐type doped silicon crystals by the Czochralski method, dislocation formation occurs frequently. The dislocation formation causes the loss of the growth ridges. Until now, it is not clear where and why the dislocations form. Therefore, heavily As‐doped crystals were studied by the means of X‐ray topography and synchrotron X‐ray topography. That way, it was possible to localize the origin of the dislocations. Abstract : During the growth of <100>‐oriented, heavily n‐type doped silicon crystals by the Czochralski method dislocation formation occurs frequently, leading to a reduction of the crystal yield. Up to now, it is not clear where and why the dislocations form. Therefore, heavily As‐doped crystals were studied in this work in more detail by means of X‐ray topography (XRT) and synchrotron X‐ray topography (SXRT). From the data obtained it is concluded that dislocations form during growth of the top cone of the crystals in the vicinity of one of the four so‐called growth ridges.